Use of camera traps to record wild red panda activity in eastern Nepal - Sonam T. Lama; Kathryn A. Bugler; James G. Ross; Adrian M. Paterson (Wildlife Society Bulletin)
Abstract Behavior of wild red panda (Ailurus fulgens) is not well‐studied, as it is difficult to locate and track individuals. Previous studies of red panda behavior have involved direct observations, finding fecal scats, and GPS collar deployment. We assessed the value of using camera traps to monitor wild red panda, evaluating the utility of placing cameras on the ground or in trees. Our study used data from 19 pairs of camera traps, set in eastern Nepal for at least a month during 2018, to monitor and compare their effectiveness for capturing wild red panda behavior at ground level and in the tree canopy. Arboreal camera traps were 8 times more effective than ground‐based cameras at capturing red pandas and their behavior in terms of frequency. Arboreal camera traps also captured images with enough clarity to distinguish facial markings between individuals and provide potential for future mark‐recapture approaches. Despite the extra set‐up difficulties and higher rate of misfires, researchers should place camera traps in tree canopies at around 5 m height for specific red panda monitoring events, including presence, activity patterns, behavior, and possible predator presence.